THE ANALYSIS OF RESEARCH OF PROJECTING, BUILDING AND OPERATION OF CARGO TERMINALS OF THE CIS AIRPORTS - Pershakov, V.N.; Vinograd, S.S.; Skalova, D.V.; Grebenyuk, E.Y.; Fesh, A.S. (Proceedings of National Aviation University (archive), 2005)
Summing up and analysis of research of projecting, building and operation of cargo complexes of CIS airports are made based on the normative documents, typical projects and existing cargo complexes.